Y = (-3/2)x + 1 is the equatjon
Answer:
SAS theorem
Step-by-step explanation:
Given
![\square ABCD](https://tex.z-dn.net/?f=%5Csquare%20ABCD)
![\[ \lvert \[ \lvert AB =\[ \lvert \[ \lvert CD](https://tex.z-dn.net/?f=%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20AB%20%3D%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20CD)
![\angle BAC = \angle DCA](https://tex.z-dn.net/?f=%5Cangle%20BAC%20%3D%20%5Cangle%20%20DCA)
Required
Which theorem shows △ABE ≅ △CDE.
From the question, we understand that:
AC and BD intersects at E.
This implies that:
![\[ \lvert \[ \lvert AE = \[ \lvert \[ \lvert EC](https://tex.z-dn.net/?f=%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20AE%20%3D%20%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20EC)
and
![\[ \lvert \[ \lvert BE = \[ \lvert \[ \lvert ED](https://tex.z-dn.net/?f=%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20BE%20%3D%20%5C%5B%20%5Clvert%20%5C%5B%20%5Clvert%20ED)
So, the congruent sides and angles of △ABE and △CDE are:
---- S
---- A
or
--- S
<em>Hence, the theorem that compares both triangles is the SAS theorem</em>
Hello! As e increases, the value of 3 will increase as well, making the answer A! Hope this helped you! :)
If their call lasts 11 minutes the cost will be the same